Identification of true hybrid progenies in cassava using simple sequence repeat (SSR) markers - Mohan, C; Shanmugasundaram, P; Senthil, N (Bangladesh Journal of Botany, 2013)
For the maping of Cassava mosaic disease (CMD) resistance gene, CO2 and MNga-1 parents were used for hybridization to develop F1 hybrid seeds and 153 progenies were planted in the field for genotyping. Out of the 75 SSR primers used for parental polymorphism, 57 produced polymorphic bands between parents and these were used to screen the 153 progenies of the cross for genotyping. Out of these 57 SSR primer pairs SSRY32, SSRY36, SSRY83, SSRY339, NS149 and NS890 loci produced single marker which clearly distinguished the parents. Based on the said six primers, 12 progenies out of 153 were identified as self pollinated seeds of CO2 female parent. So these types of SSR markers were very much useful for identification of true hybrid seedlings in the early stage of growth and genotyping of the progenies more accurately for gene mapping. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15906 Bangladesh J. Bot. 42(1): 155-159, 2013 (June)